2008
DOI: 10.1093/chromsci/46.10.867
|View full text |Cite
|
Sign up to set email alerts
|

Rapid LC--ESI-MS--MS Method for the Simultaneous Determination of Clopidogrel and its Carboxylic Acid Metabolite in Human Plasma

Abstract: A high throughput liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS-MS) method is developed for the simultaneous estimation of clopidogrel (SR25990C) and its carboxylic acid metabolite (SR26334) in human plasma using glimepiride as internal standard. The extraction of SR25990C, its metabolite, and IS from the plasma (0.3 mL) involves treatment with phosphoric acid followed by solid-phase extraction (SPE). Sample preparation by this method yields clean extracts with quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Consequently, few studies such as these have quantified the active metabolite in order to determine differences in exposure levels between patients with genotypes [5,7]. Many previous studies have reported analytical methods quantifying either parent clopidogrel [1013] or clopidogrel and its inactive metabolites (resulting from carboxyesterase activity) in an effort to measure clopidogrel active metabolite (CAM) indirectly [1418]. Another group attempted semiquantitation of underivatized CAM, using clopidogrel to establish the calibration curve [19], but this provided only an estimate of active metabolite plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, few studies such as these have quantified the active metabolite in order to determine differences in exposure levels between patients with genotypes [5,7]. Many previous studies have reported analytical methods quantifying either parent clopidogrel [1013] or clopidogrel and its inactive metabolites (resulting from carboxyesterase activity) in an effort to measure clopidogrel active metabolite (CAM) indirectly [1418]. Another group attempted semiquantitation of underivatized CAM, using clopidogrel to establish the calibration curve [19], but this provided only an estimate of active metabolite plasma concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had evaluated different pharmacokinetics (PK) methods to determine the level of the parent compound clopidogrel and its metabolites as an indicator of clopidogrel platelets inhibition [5, 99, 100]. It was found that the level of clopidogrel active metabolite is correlated with clopidogrel platelets inhibition [86, 101], and the PK of clopidogrel could be predicted by the CYP2C19 genotype [102].…”
Section: Pharmacokinetics Assessment Of Clopidogrel Responsementioning
confidence: 99%
“…The active thiol metabolite of clopidogrel is not stable which requires adding stabilizing agent within 30 seconds of blood sampling [101]. Some studies used indirect quantification of the active metabolite by quantifying the parent compound and the inactive metabolite [99, 103]. This means an accurate quantification of the active thiol metabolite in blood is difficult.…”
Section: Pharmacokinetics Assessment Of Clopidogrel Responsementioning
confidence: 99%
“…Several methods, including high‐performance liquid chromatography (HPLC), liquid chromatography mass spectrometry (LCMS), and ultra performance liquid chromatography (UPLC)‐MS were reported to analyze clopidogrel in biological matrices. Determination of the carboxylic acid metabolite of clopidogrel in human, rat plasma and serum by liquid–liquid extraction followed by HPLC have been reported .…”
mentioning
confidence: 99%
“…Determination of the carboxylic acid metabolite of clopidogrel in human, rat plasma and serum by liquid–liquid extraction followed by HPLC have been reported . Simultaneous determination of clopidogrel, its carboxylic acid, and thiol metabolites in clinical samples by liquid chromatography tandem mass spectroscopy (LC‐MS/MS) were reported . UPLC‐MS/MS was also use to determine clopidogrel in dog plasma .…”
mentioning
confidence: 99%